When Sleep is Elusive: The Spiritual Consequences and Means Towards Coping With Insomnia1. Issue 1 (May 2023) - Schwanda, Tom
Insomnia is legion in our contemporary world; yet, it is hardly a new experience. This article provides a historical review of the spirituality of insomnia. While sleep is a necessity to function well followers of Jesus from every tradition across the centuries have often practiced an asceticism that privileged their prayers over their sleep. Yet paradoxically to neglect sleep produces a myriad of consequences that weakens a person spiritually both in relation to God and others. This confronts every sleepless disciple with the decision whether they will respond with anger or acceptance of their lack of sleep. The largest section of this essay focuses on how believers sought to cope with God's "disguised sweetness" during the night watches. Their responses can be summarized primarily in two ways, proper preparation for setting the best mood for falling asleep and more difficultly how to respond when you awake and can't resume sleeping. Central to coping with insomnia is the recognition that God is the Lord of all time and is in as much control of the wakeful nights as the during the normal days.